Synthesis, Characterization and Analytical Study of Metal Complexes Derived from 1,2-Bis-(4´-Amino-2´,3´- Dimethyl-1´- Phenyl-Pyrazolinyl)- Diimino Ethane - Dhabab, J.M.; Al-Jboori, M. N.; AL-Bajalan, H. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Six transition metal complexes of Cr (III), Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) were prepared using 1,2-bis -(4-Amino-2,3-dimethyl-1- phenyl-pyrazolinyl)-diimino ethane(L) as ligand.  These complexes were characterized by elemental analysis, magnetic susceptibility, UV/VIS and FT-IR spectroscopy. These data showed that the solid complexes of Mn(II), Co(II), Zn(II) were tetrahedral geometry, and Cr(III) was octahedral while the symmetry around  Ni(II) and Cu(II) ions with the new ligand were square planar of the formula [ML]Cl2 ,  M=Ni(II) and Cu(II).              A simple method for the determination of trace amounts of copper as an example  by spectrophotometer was described based on the formation of the Cu-L  complex. The optimization were done on basis , reagent concentration , reaction time and pH medium for CuL- complex.  The molar absorptivity of the complexes at pH 9.0 , molar ratio (1:1) (L:M) at 390 nm was 0.20x104 L/mol.Cm, were determined after completion the stability of Cu(II) complex spectrophotometrically